A Ação Ordinária Coletiva para a tutela de interesses tributários - Geraldi, Guilherme Paes de Barros (2018)
The purpose of this paper is to study the use of the Ação Ordinária Coletiva (the Brazilian Class Action), a type of lawsuit provided by the Title III (Articles 81 to 104) of Law No. 8.078 / 90, the Consumer Protection Code, in claims involving Tax Law. For this purpose, the first part of this paper aims to demonstrate that the Ação Ordniária Coletiva is suitable for the protection of interests of this nature. To do so, starting with a Neo-constitutionalist notion of Law, the principle of access to justice is explored and it is demonstrated that class actions are a necessary instrument for this constitutional guarantee to be truly effective. Once the correlation between access to justice and class actions has been verified, the legal classification of the species of collective rights and the criticisms made by the Jurisprudence of this classification are analyzed, in order to conclude that the Tax Law not only can, but shall be protected by means of instruments procedures. From this point on, we will study the collective procedural instruments provided for in the Brazilian legal system and their compatibility with the protection of tax law. The conclusion that this analysis leads to is that the Ação Ordinária Coletiva, provided by the Consumer Defense Code, is among all the collective lawsuits provided by the Brazilian law, the one capable of delivering more effective judicial protection on Tax Law. The second part of this paper analyzes the operation of the Ação Ordinária Coletiva and the main obstacles encountered by the legal operators working in this area, among which are the reiterated, and unconstitutional, attempts by the Public Authorities to impose limits on effects of the judgment rendered in these actions